2018
DOI: 10.3748/wjg.v24.i10.1072
|View full text |Cite
|
Sign up to set email alerts
|

Narrow line between benefit and harm: Additivity of hyperthermia to cisplatin cytotoxicity in different gastrointestinal cancer cells

Abstract: AIMTo investigate the response to hyperthermia and chemotherapy, analyzing apoptosis, cytotoxicity, and cisplatin concentration in different digestive system cancer cells.METHODSAGS (gastric cancer cell line), Caco-2 (colon cancer cell line) and T3M4 (pancreatic cancer cell line) were treated by cisplatin and different temperature setting (37 °C to 45 °C) either in isolation, or in combination. Treatment lasted for one hour. 48 h after the treatment viability was evaluated by MTT, cell apoptosis by Annexin V-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…To the best of our knowledge, to date, there has been a lack of evidence regarding the synergy of chemotherapy and hyperthermia. In our previous studies, it was observed that gastrointestinal and ovarian cancer cells responded unpredictably following exposure to cisplatin and hyperthermia (16,31). One of the limits of this response may be the induction of cytoprotective enzymes associated with chemotherapy and/or hyperthermia, in particular HO-1.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, to date, there has been a lack of evidence regarding the synergy of chemotherapy and hyperthermia. In our previous studies, it was observed that gastrointestinal and ovarian cancer cells responded unpredictably following exposure to cisplatin and hyperthermia (16,31). One of the limits of this response may be the induction of cytoprotective enzymes associated with chemotherapy and/or hyperthermia, in particular HO-1.…”
Section: Discussionmentioning
confidence: 99%
“…Future research in the field are dedicated to the improvement of the cytostatic drugs with the help of nanotechnology (55), as well as research in the field of hyperthermia, the standardization of temperature curves and chemotherapeutic concentrations being essential (56,57).…”
Section: Discussion Perspectivesmentioning
confidence: 99%
“…First, in gastric cancer cell lines, Tang demonstrated a synergistic effect on inhibiting proliferation and induction of cell death via the apoptotic pathway [30]. In 2018, Cesna validated this synergic effect on colon cancer cells [28]. Caco-2 cells (colon cancer cell line) were treated with CDDP.…”
Section: Experimental Studymentioning
confidence: 99%
“…In vitro (Table 1) Some experimental studies demonstrated that hyperthermia can affect cell membranes, the cytoskeleton, and the synthesis of macromolecules and can increase drug-induced DNA damage and inhibit the repair of drug-induced DNA damage [28]. CDDP appeared as a drug of choice associated with hyperthermia because hyperthermia provided pharmacokinetic advantages with higher local CDDP concentrations in tissues [29].…”
Section: Experimental Studymentioning
confidence: 99%
See 1 more Smart Citation